Analysis of flapping-wing compliant mechanism - Fam, Shi Jiez (2014)
Wing inertia is the mass property that defines the torque needed by flapping-wing creatures to accelerate and decelerate the wings. During flapping flight, flapping-wing Micro Aerial Vehicle (MAV) invests inertial power to move the wings due to the presence of the wing inertia. This directly leads to larger power consumption in the flapping-wing MAV. By integrating elastic elements for energy storage into the flapping-wing MAV's joints, power requirement of the MAV can be eventually reduced. At the end of each wing stroke, the elastic elements at the joints would be deformed and elastic strain energy would be stored in them. The elastic energy stored would then be converted to kinetic energy to assist in returning the wing and in this manner, the inertial power required can be greatly reduced. The characteristic of the design can be found out by performing the dynamic analysis. In the analysis, mathematical modeling is used to construct a governing equation that describes the behavior of the flapping-wing prototype. The governing equation is capable to predict certain characteristic of the prototype, which includes the power consumption which we desired to know. By knowing these information, the design of the prototype is possible to be improved to be more power efficient. To judge if the governing equation is effective, the generated results from the governing equation would be compared with the corresponding experiment data. Other than that, power analysis would also be carried out to see how well the elastic elements can recover the inertial power in the flapping process.